KARAKTERISTIK PEKERJA KOMUTER PEREMPUAN YANG MENGALAMI PERJALANAN DURASI PANJANG JABODETABEK 2019 - Muhammad Ali Irfan; Rani Nooraeni (Seminar Nasional Official Statistics, 2020)
Women have an important role in both the family and society. The increasing role of women in the workforce shows the higher motivation of women to work because of better education. In general, a person will minimize his travel time. However, 28 percent of commuters in Greater Jakarta traveled 90 minutes or more. In fact, women's travel patterns are relatively shorter due to household responsibilities. Long-duration commuting that is carried out continuously can be bad for life, and women are more at risk of being affected. This issue needs to be further investigated to find out what characteristics are driving female commuter workers on long-duration commuting. The method used is a binary probit regression. Based on the results of the study note that the level of education, income level, mode of transportation, and homeownership status positively affect the long-duration commuting. The state needs to pay attention to the welfare of its population, including women. With this research, it is hoped that solutions can be given so that women can travel shorter so that the impact of long-duration commuting can be minimized and still be able to provide maximum benefits for their families and work.